MANAJEMEN MUTU PENDIDIKAN FATIH BILLINGUAL SCHOOL ACEH - Dian Ayuningtyas; Ayuningtyas, Dian; Rahmad Syah Putra (Program Studi Manajemen Pendidikan Islam, 2023)
Improving the quality of education is a must to meet the needs of the school and community. This study aims to determine the planning, implementation, monitoring and evaluation of programs to improve education. The method used in this research is descriptive method with qualitative approach. Data collection techniques: observation, interviews and documentation study. Subjects were Principal, Vice Principal, committees and supervisors. The results of the study will describe how Planning, Implementation, and Evaluation of education quality improvement programs are carried out by Fatih Billingual School in Aceh every year, but also conducted on a monthly and semester basis. includes internal evaluation and external evaluation as a reference for improving the quality of schools in Aceh.